PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI PEMODERASI - Sianipar, Ruth Tridianty; Sembiring, Lenny Dermawan; Silitonga, Hery Pandapotan (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
Investors ineed iinformation iabout ithe icompany's iperformance ito imake iinvestments. iThe icompany's ivalue iis ithe ichoice iof iinvestors iin igetting ithat iinformation. iThe ipurpose iof ithis istudy iis ito idetermine ithe ieffect iof iprofitability ion ifirm ivalue, iand iwhether icapital istructure ican imoderate iprofitability ion ifirm ivalue. iData ianalysis itechniques iwith ithe iclassical iassumption itest, imultiple ilinear iregression, ihypothesis itesting icoefficient iof idetermination, iand iModerated iRegression iAnalysis i(MRA). iThe iobjects iin ithis istudy iare icompanies iin ithe iOil iand iGas iMining iSub-Sector ithat iare iListed ion ithe iIndonesia iStock iExchange ifor ithe iperiod i2012 i- i2018. iThe iresults iof ithis istudy ifound ithat isimultaneous iROA iand iROE isignificantly iinfluence iTobin's iQ. iPartially iROA ihas ipositive iand inot isignificant ieffect ion iTobin's iQ, iand iROE ihas ipositive iand isignificant ieffect ion iTobin's iQ. iThe iMRA itest iresults iobtained iLtDER iresults ido inot imoderate ithe ieffect iof iROA iand iROE iAgainst iTobin's iQ. iThe icoefficient iof idetermination inamely iROA iand iROE ican ibe iexplained iby iTobin's iQ iby i66.3%. iCompanies imust ibe icareful iin iusing idebt ito iincrease itheir iactivities, ibecause ithe iuse iof iexcess idebt ihas ithe ipotential ifor ibankruptcy. Keywords: LtDER, ROA, ROE, Tobins Q